Evaluation of Groundwater Quality using the GQI Index for Drinking Purposes - Mojtaba Khoshravesh; Seyed Mohammad Reza Hosseini Vardanjani; Hajar Taheri Soudjani; Marzieh Ghahreman (پژوهشنامه مدیریت حوزه آبخیز)
Extended Abstract Background: The use of groundwater for agricultural, industrial, and drinking purposes is significantly increasing worldwide. These resources are considered an important part of the renewable water ecosystem and have various advantages over surface waters, such as higher quality and less contamination. However, recent intermittent droughts and a noticeable decrease in surface water resources have led to the excessive use of groundwater sources and a decline in their quality. Therefore, understanding the quality of groundwater is crucial for proper planning and management of these resources and requires serious attention and detailed analysis. Additionally, one of the health problems in developing areas is the lack of access to safe drinking water, and human health is at the core of sustainable development in the region. Therefore, ensuring the welfare and health of the community at an acceptable level is not possible without access to clean and standardized drinking water. Water is important from both health and economic perspectives as it serves as a catalyst for industrial growth and the prosperity of the agricultural sector. In this regard, this research aims to evaluate and analyze the quality and spatial changes in groundwater quality based on the GQI assessment index. Methods: This research focuses on evaluating and analyzing spatial changes in groundwater quality within the study areas of Khanmirza, Lordegan, Boroujen, Ardal, and Kiar, located in  Chaharmahal and Bakhtiari province, for drinking purposes. Practical information is provided regarding the status of available water resources in the region for drinking purposes. To this aim, 28 groundwater samples were collected from legally operating wells in various locations within the mentioned counties during the  2020-2021 period and subjected to chemical analysis in the laboratory. The GQI (Groundwater Quality Index) was used to assess the quality of these samples for drinking purposes. In this study, the GQI was calculated based on the concentration values of 11 parameters, including electrical conductivity, acidity, total dissolved salts, calcium ion, sodium, magnesium, potassium, carbonate, bicarbonate, chloride, and sulfate. Subsequently, spatial zoning of the overall parameter values was performed using the chemical characteristics of the collected samples and employing the inverse distance weighting (IDW) interpolation method in the GIS software environment, and the desired information layers were obtained in raster format. Furthermore, overlays were performed by applying computational functions to the available information layers,, followed by estimating the GQI values and preparing raster maps of the index. The output maps can be utilized not only to determine the qualitative characteristics within the study area but also to analyze the trends of their variations, prepare zoning maps for  each parameter, and compare them with standard values.